Motywy ukraińskie w polskiej muzyce gitarowej XIX wieku - Gurgul, W. (Народна творчість та етнологія, 2022)
Elementy ludowej muzyki ukraińskiej pojawiają się w polskiej literaturze gitarowej od początków XIX wieku, zarównoElementy ludowej muzyki ukraińskiej pojawiają się w polskiej literaturze gitarowej od początków XIX wieku, zarównow literaturze na gitarę angielską, jak i hiszpańską. Obecne były i w twórczości tuzów XIX-wiecznej polskiej gitarystyki(Feliks Horecki, Jan Nepomucen Bobrowicz), jak również w literaturze komponowanej przez mniej znanych lub obecniecałkowicie zapomnianych twórców (Eduard Salleneuve, Cyprian Leonowicz, Jan Rywacki). Twórcy sięgali głównie po stylizowanetańce (kozak) oraz melodie ludowe, ujmując je w proste techniczne opracowania przeznaczone do muzykowaniadomowego lub opierając na nich kompozycje wirtuozowskie. Niniejszy artykuł nakreśli obecność ukraińskiego folkloruw polskiej muzyce gitarowej XIX wieku – tematykę wcześniej niepodejmowaną w badaniach nad polską gitarystyką. The elements of Ukrainian folk music appeared in Polish guitar music in the early 19th century, both in music for English guitar tuned in G major (sources for this instrument appeared chronologically first) and for 6-string Spanish guitar. Composers have used stylized dances, mainly kozachok, for composing simple technical arrangements intended for domestic parlour music. Apart from four anonymous manuscripts for English guitar, there are two anonymous kozachoks in manuscripts from the National Library of Poland in Warsaw and the Princes Czartoryski Library in Krakow and one kozachok by Eduard Salleneuve. Also another form – duma/dumka – is popular among 19th-century Polish guitarists; it has appeared both in the solo and in the original version, intended for vocal with accompaniment. The authors of dumka are, among others Jan Rywacki, and anonymous dumas are preserved in the Jasna Góra Monastery (Library of the Pauline Fathers in Częstochowa), the Jagiellonian Library in Krakow and in the mentioned Princes Czartoryski Library. Solo improvised dumkas have been performed by the greatest Polish 19th-century virtuosos – Stanisław Szczepanowski and Marek Konrad Sokołowski, as evidenced by extensive press coverage. Three composers – Jan Nepomucen Bobrowicz, Felix Horetzky, and the less-known Cyprian Leonowicz – also used the Ukrainian folk melodies, mainly as a basis for virtuoso sets of variations. Leonowicz’s piece, which is a kind of written improvisation, is based on the famous song Ikhav Kozak za Dunaj. The melody used by Bobrowicz is more difficult to identify, although the title of the piece indicates the Ukrainian element – Air d’Ukraine varié. Horecki arranged two melodies, including the song Ikhav Kozak za Dunaj, in technically simple arrangements. The Ukrainian thread also appears in the biographies of some 19th-century Polish guitarists, including Sokołowski, Numa Łepkowski, and Karol de Wyhowski. This article shows that Ukrainian folklore was the strongest foreign element in Polish guitar music of the 19th century. Areas requiring further research are also indicated – related to little-known sources(such as guitar manuscripts from Jasna Góra, the Jagiellonian Library, or from the collection of Oskar Kolberg), as well as those concerning Ukrainian guitar music from the 19th century, practically unknown outside Ukraine.